MicroRNA-mediated stress response in bivalve species - Haitham G. Abo-Al-Ela; Caterina Faggio (Ecotoxicology and Environmental Safety, 2021)
Bivalve mollusks are important aquatic organisms, which are used for biological monitoring because of their abundance, ubiquitous nature, and abilities to adapt to different environments. MicroRNAs (miRNAs) are small noncoding RNAs, which typically silence the expression of target genes; however, certain miRNAs directly or indirectly upregulate their target genes. They are rapidly modulated and play an essential role in shaping the response of organisms to stresses. Based on the regulatory function and rapid alteration of miRNAs, they could act as biomarkers for biotic and abiotic stress, including environmental stresses and contaminations. Moreover, mollusk, particularly hemocytes, rapidly respond to environmental changes, such as pollution, salinity changes, and desiccation, which makes them an attractive model for this purpose. Thus, bivalve mollusks could be considered a good animal model to examine a system’s response to different environmental conditions and stressors. miRNAs have been reported to adjust the adaptation and physiological functions of bivalves during endogenous and environmental stressors. In this review, we aimed to discuss the potential mechanisms underlying the response of bivalves to stressors and how miRNAs orchestrate this process; however, if necessary, other organisms’ response is included to explain specific processes.